Main stages of implementation models of human qualities in students during physical education forming realization - Гуменюк, С. В. (Slobozhanskyi Herald of Science and Sport, 2011)
The article covers the main stages of implementation models of human qualities in students during physical education: presentation of human qualities, creating a positive attitude to human qualities, the formation of humane attitudes and beliefs and establishment of human behavior.